Troubled Weather Satellite Program. - Barlas, S.
Cost overruns and project delays have led to a cloudy forecast for the United States' new polar-orbiting weather satellites. The greatly upgraded satellites, to consist of a group of three with three replacements, are meant to beam back weather data that would enable scientists to better predict hurricanes and military plans. This paper discusses the problems with the three new polar orbiting weather satellites mainly due to delayed schedule and cost overruns. These problems are a major concern for the whole enterprise of monitoring Earth from outer space. Also, delays in critically needed polar instruments could affect all of US environmental monitoring
Keywords: Earth monitoring; US environmental monitoring; Cost overruns; Military applications; Polar orbiting weather satellites; Project delays; Satellite replacements; Satellite upgrades; Weather data prediction